The principle of translation - Frank, Joachim (Henry Stewart Talks, 2007)
Composition of the ribosome, Principle of translation, The four phases of translation, Structure and function of small and large ribosomal subunits, Role of elongation factors, The paths of messenger RNA, transfer RNA and the nascent polypeptide, Elongation cycle and binding positions of elongation factors, Decoding, peptidyl transfer and translocation, Phylogenetic conservation of ribosomal architecture